Cheese. Major Cheese Groups - Fox, P. F. (Elsevier, 2004)
The market for cheese as a food ingredient has increased rapidly in recent years and now represents upto approximately 50% of cheese production in some countries. Volume II entitled Major Cheese Groups will focus on major cheese groups which is devoted to the characteristics of the principle families of cheese. Cheese: Chemistry, Physics, and Microbiology Two-Volume Set, 3E is available for purchase as a set, and as well, so are the volumes individually. *Reflects the major advances in cheese science during the last decade *Produced in a new 2-color format *Illustrated with numerous figures and tables.